AN UNUSUAL CASE OF IPSILATERAL SHOULDER AND ELBOW DISLOCATION - Mohapatra, Ashutosh; Choudhury, Priyam (Journal of Ayub Medical College Abbottabad, 2021)
A 34 years old male, labourer by occupation was brought to our trauma centre in an inebriated state with a history of fall from a height of approximately 10 feet. He complained of pain in the right elbow. A complete examination of the affected upper limb revealed an ipsilateral anterior shoulder dislocation and a posterior elbow dislocation with no other concomitant injuries. Both the dislocations were reduced conservatively and the patient was successfully managed. The patient is absolutely fine now, 6 months post his dislocation and has resumed back to his work. This case has been presented to highlight the rare and unusual nature of the injury, since ipsilateral dislocation of shoulder and elbow occur infrequently.